The Association Between Maternal Education, Family Income, House Sanitation, and the Incidence of Acute Respiratory Tract Infection in Children Under Five - Anita Sri Sulistyo; Didik Tamtomo; Ambar Mudigdo (Journal of Epidemiology and Public Health, 2016)
Background: It was estimated that the incidence of Acute Respiratory Tract Infection (ARTI), including pneumonia, was  10-20% in children under five in Indonesia. Therefore ARTI in children under five is a public health important that calls for control and prevention. The purpose of this study was to determine the association between maternal education, family income, house sanitation, and the incidence of ARTI in children under five.Subjects and Method: This was an analytic observational study with case control design. This study was conducted in Wonogiri 1 and Kismantoro Health Centers, Wonogiri, Central Java, from September to October, 2016. A total sample of 200 children under five were selected for this study by fixed disease sampling, consisting of 100 children with ARTI and 100 children without ARTI. The dependent variable was pneumonia. The independent variables were maternal education, family income, house component, and house sanitation. The data were collected by a set of questionnaire, checklist, and medical record at the health centers. The data were analyzed by multiple logistic regression.Results: Maternal education ≥senior high school (OR=0.09; 95% CI= 0.03 to 0.22; p<0.001),  house component meeting the required standard (OR=0.27; 95% CI= 0.13 to 0.57; p<0.001), and good house sanitation (OR=0.15; 95% CI= 0.06 to 0.38; p<0.001) were associated with decreased risk of pneumonia in children under five, and they were statistically significant. The association between family income and the risk of pneumonia was not statistically significant (OR=0.87; 95% CI= 0.42 to 1.79; p=0.703).Conclusion: Maternal education ≥senior high school, house component meeting the required standard, and good house sanitation are associated with decreased risk of pneumonia in children under five.Keywords: maternal education, family income, house sanitation, pneumonia, children under five Correspondence: Anita Sri Sulistyo. District Health Office Wonogiri, Central Java. Email: anitasrisulistyowati@yahoo.comJournal of Epidemiology and Public Health (2016), 1(3): 195-202https://doi.org/10.26911/jepublichealth.2016.01.03.06